2016
DOI: 10.1093/gji/ggw441
|View full text |Cite
|
Sign up to set email alerts
|

GRACE era variability in the Earth's oblateness: a comparison of estimates from six different sources

Abstract: We study fluctuations in the degree-2 zonal spherical harmonic coefficient of the Earth's gravity potential, C 20 , over the period 2003-2015. This coefficient is related to the Earth's oblateness and studying its temporal variations, C 20 , can be used to monitor large-scale mass movements between high and low latitude regions. We examine C 20 inferred from six different sources, including satellite laser ranging (SLR), GRACE and global geophysical fluids models. We further include estimates that we derive fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 86 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…Chen et al 2007Chen et al , 2013bRiva et al 2009;Chambers & Willis 2010;Rio et al 2011;Schrama et al 2014;Ries 2015, personal communication). The reliability of SLR-derived C 20 has been demonstrated by Chen & Wilson (2008 and by Meyrath et al (2016). The SLR C 20 time-series solution used here is from M.K.…”
Section: Introductionmentioning
confidence: 85%
“…Chen et al 2007Chen et al , 2013bRiva et al 2009;Chambers & Willis 2010;Rio et al 2011;Schrama et al 2014;Ries 2015, personal communication). The reliability of SLR-derived C 20 has been demonstrated by Chen & Wilson (2008 and by Meyrath et al (2016). The SLR C 20 time-series solution used here is from M.K.…”
Section: Introductionmentioning
confidence: 85%
“…They also showed that these variations are consistent with the last decade observed long-term tendency of the geoid oblateness, the so-called J 2 parameter. J 2 time variations have been observed and studied for more than 30 years (e.g., Yoder et al, 1983;Cheng et al, 2011;Ivins et al, 1993;Meyrath et al, 2017;Mitrovica & Peltier, 1993;Nakada et al, 2016;Trupin, 1993). It is well accepted today that the J 2 long-term variations are most probably induced by glacial isostatic adjustment (GIA) and recent ice melting (RIM) (e.g., Ivins et al, 1993;Mitrovica & Peltier, 1993;Trupin, 1993;Cox and Chao, 2002;Dickey et al, 2002;Nerem & Wahr, 2011;Cheng et al, 2013;Nakada et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, a consideration of only elastic Earth's properties implies that viscoelastic solid Earth signals, such as glacial isostatic adjustment (GIA), are ignored. have demonstrated that a sufficiently accurate J 2 time series can be obtained from GRACE data supported by an oceanic C 20 coefficient time series, derived from ocean bottom pressure (OBP) variations by an ocean circulation model (Meyrath et al, 2017). The recently ended Gravity Recovery And Climate Experiment (GRACE) satellite mission monitored changes in the Earth's gravity field for almost 15 years .…”
Section: Introductionmentioning
confidence: 99%
“…For more than four decades, J 2 has been monitored by satellite laser ranging (SLR; Cheng et al, 2013). In the last 20 years, new data types, platforms, and methodologies have become available, and this enables comparisons between different solutions (Meyrath et al, 2017). Under the assumption that the Earth deforms elastically (Blewitt, 2003), seasonal J 2 variations can be derived from Global Positioning System-detected solid Earth deformations (Gross et al, 2004;Lavallée et al, 2010) or Earth's rotation variations (Chen & Wilson, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation